Antigone and productivity of the negative: the political act and tha paradox of ethics (Andamios, Revista de Investigación Social, 2016)
Informed by Lacan’s reading of the Sophocles’ tragedy Antigone, this paper will explore the political limits of an ethical act determined by perseverance in desire. The tragedy of Antigone can be considered to be an ethical and political act insofar that suspension of the symbolic coordinates that support the organization of law and community is produced, thereby allowing the restructuring of political space. The morbidity of desire, i.e. its inseparable relationship to death, mobilizes a paradoxical productivity that, without actually filling the immanent void of the symbolic field, allowing a continuous creation ex nihilo in which a society can discuss its organization of relations and political significations.
Keywords: Tragedy; psychoanalysis; negativity; ethical paradox; politics